Лінгвокультурний концепт ВИНО в українській мовній картині світу - Шитик Людмила; Sitik Lyudmila; Liudmyla Shytyk; Юлдашева Людмила; Juldaseva Lyudmila; Liudmyla Yuldasheva (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Резюме. Статтю присвячено дослідженню концепту як одного з ключових лінгвістичнихпонять. Запропоновано огляд різних підходів до визначення поняття "концепт", окреслено його роль у формуванні національноїконцептосфери.Зауважено, щозацікавленнянауковців лише окремимиаспектамививчення концептосфери "їжа"зумовлює необхідність цілісного дослідження лінгвокультурного концепту ВИНО, вивчення мовних одиниць у синтезі їхньої семантичної і функційної специфіки, виявлення особливостей породження мовного знака, а також потребу в окресленні лінгвосеміотичних і лінгвокультурних параметрів концепту, засвідчених передусім у літературних зразках і пареміях. Актуальність обраної теми зумовленанеобхідністю розширитийсуттєво поглибитизнанняпро мовну репрезентацію лінгвокультурного концептуВИНО, його роль уформуванні моделі української ментальності, що допомагає виявити способи взаємодії вербального та культурного кодів нації.Мета наукової праці –дослідження лінгвокультурної специфіки концепту ВИНОв українській мовній картині світу. У студії з’ясованосутність поняття "лінгвокультурний концепт"і "гастрономічний дискурс"; визначенолінгвокультурний зміст українських паремій із концептом ВИНО; проаналізованосинтагматичні зв’язки імені концепту. Наукова новизна роботи полягає в тому, що в нійдослідженолінгвокультурнийконцепт ВИНОв українській мовній картині світу. Набуло подальшого розвитку з’ясування особливостей лінгвокультурного концепту та гастрономічного дискурсу, визначено лінгвокультурний зміст паремій із концептом "вино"та схарактеризовано синтагматичні зв’язки імені концепту. У перспективі передбачено дослідження лінгвокультурноїспецифіки інших концептів, пов’язаних із гастрономічним дискурсом.

A tanulmány a fogalom mint a nyelvészet egyik kulcsfontosságú koncepciójának kutatásával foglalkozik. Bemutatja a „fogalom” meghatározásához kapcsolódó különböző megközelítések jellemzőit, valamint a fogalom szerepét a nemzeti koncepcionális szféra kialakulásában.A tanulmány rámutat, hogy a tudósok kitartó érdeklődése az „élelmiszer” koncepcionális szféra bizonyos aspektusai iránt szükségessé teszi a BOR nyelvi-kulturális fogalmának holisztikus vizsgálatát, a nyelvi egységek vizsgálatát szemantikai és funkcionális sajátosságaik szintézisében, a nyelvi jelek létrehozása sajátosságainak azonosítását, valamint a fogalom nyelvi-szemiotikai és nyelvi-kulturális paramétereinek a körvonalazását, melyeket elsősorban az irodalmi minták és a parémiák igazolnak.A választott téma relevanciáját az határozza meg, hogy bővíteni kell és jelentősen el kell mélyíteni az ismereteket a BOR nyelvi-kulturális fogalom nyelvi reprezentációjáról az ukrán mentalitás modelljének kialakításában, ami segít feltárni a nemzet verbális és kulturális kódjai közötti interakció módjait.A tudományos munka célja a BOR fogalma nyelvi és kulturális sajátosságainak vizsgálata az ukrán nemzeti nyelvi világképben. A tanulmány tisztázza a „nyelvi-kulturális fogalom” és a „gasztronómiai diskurzus” fogalmának lényegét; meghatározza az ukrán nyelvi elemeknek a BOR fogalmával kapcsolatos nyelvi és kulturális tartalmát; elemezi a fogalom nevének szintagmatikus kapcsolatait.A munka tudományos újdonsága abban rejlik, hogy a BOR nyelvi és kulturális fogalmát vizsgálja az ukrán nyelvi világképben. A nyelvi és kulturális fogalom és a gasztronómiai diskurzus sajátosságainak vizsgálatát továbbfejlesztette, meghatározta a „bor” fogalommal ellátott parémiák nyelvi és kulturális tartalmát, valamint jellemezte a fogalomnév szintagmatikai viszonyait. A jövőben a gasztronómiai diskurzushoz kapcsolódó egyéb fogalmak nyelvi és kulturális sajátosságainak vizsgálatát tervezzük.

Abstract. The article deals with the research of the concept as one of the key linguistic notions. The characterization of different approaches to the definition of the notion in "concept"is suggested. The role of the concept in the formation of the national conceptual sphere is discussed. It is noted that the persistent interest of scientists only in certain aspects of the study of the conceptual sphere of "food" necessitates a holistic study of the linguistic and cultural concept of WINE, the study of language units in the synthesis of their semantic and functional specificity, the identification of the peculiarities of the generation of a linguistic sign, as well as the need to outline linguosemiotic and linguocultural of the parameters of the concept, evidenced primarily in literary samples and paremias. The relevance of the chosen topic is determined by the need to expand and significantly deepen knowledge about the linguistic representation of the linguistic and cultural concept WINE in the formation of a model of the Ukrainian mentality, which helps to reveal ways of interaction between the verbal and cultural codes of the nation.The purpose of the scientific work is to study the linguistic and cultural specificity of the concept of WINE in the Ukrainian National Linguistic World view. The essence of the concept of "linguistic and cultural concept"and "gastronomic discourse"was clarified in the studio; the linguistic and cultural content of Ukrainian pairs with the concept of WINE is determined; the syntagmatic relations of the name of the concept were analyzed; the mechanism of respondents’perception of the WINE concept was investigated.The authors researche into the concept WINE(vyno) in Ukrainian linguistic worldview.The scientific novelty of the work lies in the fact that it examines the linguistic and cultural concept of WINEin the Ukrainian linguistic picture of the world. In the work, the elucidation of the features of the linguistic and cultural concept and gastronomic discourse was further developed, the linguistic and cultural content of paremy with the concept WINE was determined, and the syntagmatic connections of the name of the concept were investigated.In the future, we plan to investigate the linguistic and cultural specificity of other concepts related to the gastronomic discourse.
A BOR nyelvi és kulturális fogalma az ukrán nyelvi világképben
The Linguistic and Cultural Concept of WINE in Ukrainian National Linguistic Worldview linguistic picture of the world
https://aab-philologica.kmf.uz.ua/aabp/issue/view/5/9
Keywords: лінгвокультурний концепт ВИНО; гастрономічний дискурс; ім’я концепту; паремії; синтагматичні зв’язки